KAJIAN PENGELOLAAN MANGROVE DI DESA JENU, KECAMATAN JENU, KABUPATEN TUBAN, JAWA TIMUR - Raka Nur Sukma (Fakultas Perikanan Universitas Pekalongan, 2017)
Mangrove rehabilitation activities are often done in Indonesia, but often fail. The several factors often lead to failure is, unattended reforestation, lack of coordination among related institutions, and lack of community participation. The methode in this study is evaluation by percentage analysis. The results showed that the physical condition in the village of Jenu in accordance with the growth of mangrove, with texture of substrate sand. The role of government institutions in the village of Jenu is good enough, by nurturing and directing the community to understand the importance of mangrove forests, in addition the community is also directed to form a farmer group with the name of wanamina bahari.Key word ; Mangrove, rehabilitation, reforestation activities.